Patient with bilateral cleft lip and palate, anterior crossbite and severe maxillary compression treated with early orthodontics, Hyrax and orthognathic monomaxilar surgery. Case report - Barhoum, Habib; León, María-del Pilar; Benjumea, Neftalí-Joaquín (Revista Estomatología, 2016)
This article reports an orthodontic - surgical treatment of a patient with bilateral cleft lip and palate in clinical Lip and Palate at Valle´s University. The patient had a bad skeletal and Angle Class III occlusion with anterior and posterior cross bite with severe maxillary constriction, posterior mandibular rotation and floating premaxilla. The malocclusion was corrected by standard fixed appliances 0.022x0.028 inch slot, Hyrax in the maxila and mandibular setback and advance chin finally. In addition to oral rehabilitation patient to determine an aesthetic front in the upper anterior and improve the results regarding the mini and micro aesthetics of the case.